Maspin enhances cisplatin chemosensitivity in bladder cancer T24 and 5637 cells and correlates with prognosis of muscle-invasive bladder cancer patients receiving cisplatin based neoadjuvant chemotherapy. Issue 1 (December 2016) - Chen, Jinbo; Wang, Long; Tang, Yunhua; Gong, Guanghui; Liu, Longfei; Chen, Minfeng; Chen, Zhi; Cui, Yu; Li, Chao; Cheng, Xu; Qi, Lin; Zu, Xiongbing
Abstract Background Maspin, a non-inhibitory member of the serine protease inhibitor superfamily, has been characterized as a tumor suppressor gene in multiple cancer types. Chemotherapeutic insensitivity is one of major obstacles to effectively treating muscle invasive bladder cancer (MIBC). This study was conducted to investigate the role and probable mechanism of Maspin enhancing cisplatin chemosensitivity of bladder cancer in vitro and MIBC patients. Methods Maspin expression was quantified by qRT-PCR in two MIBC cell lines (T24 and 5637). After successful established Maspin overexpression model by lipidosome transfection, MTT and cell apoptosis assay were used to assess the MIBC's cisplatin sensitivity. Western blot method was used to test PI3K/ AKT/mTOR signal passway and apoptosis related molecules Caspase3 and Bcl-2. Additionally, we evaluated Maspin expression and prognosis in 62 MIBC cases who underwent cisplatin based neoadjuvant chemotherapy (NACT) using immunohistochemistry. Result Upregulate Maspin expression could enhance the chemosensitivity induced by cisplatin in T24 and 5637 cell lines. The cell viability, cloning ability and IC50 were reduced while apoptosis rate was upregulated when cells were transfected Maspin. Phospho(p)-AKT, PI3K, mTOR, and Bcl-2 expression were significantly decreased, whereas Caspase3 was greatly increased in the Maspin group. In the clinic study, there was significant correlation between Maspin expression and overall survival (OS) and progression-free survival (PFS) rate in MIBC patients who received cisplatin based NACT. Conclusion Maspin could enhance cisplatin chemosensitivity in T24 and 5637 cell lines. Its expression correlated with prognosis of MIBC patients who received cisplatin based neoadjuvant chemotherapy.